Me For You: Lessons About Everyday Video Messaging From Skype Qik - Rintel, Sean; Harper, Richard; Watson, Rod; O'Hara, Kenton (CHI 2015, 2015)
In this position paper we outline the opportunities and challenges of pure asynchronous video messaging as an everyday utility. We recruited 53 users to try Skype Qik ‘in the wild’ for two weeks from its launch in October 2014. We found users orienting to an organizational principle that we term ‘Me For You’, a self-conscious yet creative orientation that allowed users to transform features of their everyday affairs into show-about-ables that can be subject to and warrant the interrogative gaze of a Qik recipient. We found that such acts implied a reciprocity that was valuable in some special contexts, while at other times proving dissonant with assumptions about mundane communicative practices between particular parties. To warrant another’s gaze requires artfulness, but in some relationships one might not want to demand that artfulness in return. We argue that richness is not a matter of mode but of perceived control, within which the morality of gaze represents an ongoing challenge for designing everyday telepresence.
CHI 2015 Workshop on Everyday Telepresence: Emerging Practices and Future Research Directions